Система низькочастотного імпульсного навантаження синхронного генератора з постійними магнітами в автономних вітроенергоустановках - Щур, Всеволод Ігорович (НТУ "ХПІ", 2013)
In order to reduce the cost of wind turbines and to extend its functionality, accumulation of generated energy as heat is proposed. For to control the electrical load of generator, low-frequency pulse control by connection of the electric heaters is used. A mathematical model of wind turbine with pulse load control is developed and optimal parameters of the system are selected. The efficiency of the developed optimal control system of wind turbine generator loading was confirmed by the computer simulation.
Low Frequency Pulse Loading System of Permanent Magnet Synchronous Generator for Stand-alone Wind Turbines
Keywords: вітрова енергетика; здешевлення автономної ВЕУ; термоелектричні нагрівачі; вітроротори; синхронні генератори; система електричного навантаження